Study on the mixed elasto-hydrodynamic lubrication characteristics of dynamically loaded journal bearings considering journal misalignment - CAO Xi; TANG Xingbo; CHE Changfei; LIAO Jianfeng; FENG Chengke; ZHANG Chengyao; XIONG Guoqing (Jixie chuandong, 2025)
ObjectiveIn response to the unclear lubrication characteristics of dynamically loaded journal bearings under misaligned journal states, a mixed elasto-hydrodynamic lubrication model for dynamically loaded journal bearings considering journal misalignment was constructed.MethodsBased on the transient mixed lubrication model of journal bearings, the oil film thickness under journal misalignment was modified, and a metal surface roughness peak elastoplastic contact model was introduced to further couple the dynamics equation of the journal center with time-varying loads. A numerical solution scheme and model convergence conditions were designed to achieve lubrication simulation of dynamically loaded journal bearings with journal misalignment.ResultsThe results show that as the misalignment angle of the journal increases, the maximum oil film pressure and rough contact pressure significantly increase, exhibiting a specific nonlinear law. The minimum oil film thickness shows an approximately linear decrease, and the pressure and oil film distribution show significant non-uniformity with the increase of misalignment angle. The axis trajectory reflects that the journal’s position in the misaligned state is lower than that in the alignment state of the journal.